Impact of physical module (adventure-based activity) of Malaysia's National Service Training Programme on team cohesion - Zakaria, Jaffry (2012)
The National Service Training Programme better known as Program Latihan Khidmat Negara (PLKN) was launched by the government on the 16th of February 2004 to foster national unity and integration. However, since its inception, no specific empirical study has been conducted on the physical activity module (adventure-based activity) to measure the effectiveness of the programme in improving the process of national unity and integration. Therefore, the present research attempts to measure the effectiveness of physical activity module of the programme which consists of the adventure-based activity curriculum and to study the effects of outdoor activities on team cohesion among the participants of the programme at three camps namely, Tasik Meranti Camp, Tasoh Camp and Guar Chenderai Camp in the state of Perlis, Malaysia. Pre and post-test were conducted in order to investigate the effects of adventure-based activity towards cohesiveness among participants in groups at the camps. The study also explores the influence of socio-demographic variables (age, gender and place of residence), physical activities as well as interpersonal relationships among the participants towards improving team cohesion. Herein, respondents comprised of a total of 994 participants. A modified Group Environment Questionnaire (GEQ) was used to collect the required data which was administered during the pre and post-test at the respective camps. The GEQ measured four different dimensions: (1) Group Integration-Task (GI-T), (2) Group Integration-Social (GI-S), (3) Individual Attractions to the Group-Task (ATGT) and (4) Individual Attraction to the Group-Social (ATG-S). Among the four subscales, Individual Attractions to the Group-Task (ATG-T) was found to be most significant while Group Integration-Task (GI-T) sub-scale were found to be not significantly different between the pre and post-test. Nevertheless, after the physical activity curriculum at the camps was accomplished, team cohesion was successfully developed in all sub-scales investigated. The data collected was analyzed using the Statistical Package for Social Science (SPSS). The statistical analysis of GEQ on the pre and post-test proved that team cohesion among the participants was achieved and significantly different during pre and post-test. Concisely, it can be concluded that the physical activity module (adventure-based activity) had increased the level of participants’ group cohesiveness and resulted in positive group binding. Participants showed shared vision and unity of purpose, developed complementary roles and synergistic teamwork, displayed strong internal leadership and effective communication. Overall, the present study found that physical module (adventure based activity) in the National Service Training Programme (PLKN) was effective in developing cohesion and integration among participants. The study also indicated that there was a positive correlation between the Group Development Component and the Theory of Group Development as propounded by Tuckman (1965).